Governança dos recursos hídricos: caso da bacia do Rio Pitimbu - Câmara, Renata Godeiro Carlos (2016)
The creation of the River Basin Councils (RBC) in Brazil, as established in the Brazilian Water Resources National Policy, represented a relevant legal advance in water resources management. RBC point to an advance towards legitimacy, because they may open a relevant space to social participation in water resources management. However, water management efficacy implies the existence of an institutional arrangement that promotes social participation. The Pitimbu River Basin is located at the Natal urban region, and comprises partly the municipalities of Macaíba, Parnamirim and Natal. Despite of its strategic importance as potable water supply, Pitimbu River has been adversely impacted by urbanization, which affects fluvial system and water resources. In this context, this study is aimed at analyzing current institutional capacity in providing social participation mechanisms that can promote a sustainable water and land use management. For this purpose, semi-structured interviews were applied to eleven members of the RBC. Obtained data was analyzed qualitatively using the MAXQDA® software. Obtained results revealed that current institutional arrangement fails in recognizing RBC as a key element in water resources management, as established in the 9433/97 Act. It was observed some relevant RBC characteristics: a) poor civil society participation in the RBC; b) public sector participation in the RBC is predominant; c) an updated River Basin Water Plan is lacking; d) most of the RBC meetings prioritize internal and bureaucratic issues; e) the inexistence of a Basin Agency justifies the lack of funding; f) RBC political power in decision making process is lacking. Furthermore, articulation between government levels is poor and explains a condition of disorganization in water resources management. It was observed the need of a broad institutional reform that stimulates the implementation of management instruments. Finally, political power decentralization, social participation mechanisms, and State modernization still represent challenges to be attained.